2008
DOI: 10.3892/ijmm.21.6.705
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-two new cases with small supernumerary marker chromosomes detected in connection with fertility problems: Detailed molecular cytogenetic characterization and review of the literature

Abstract: Thirty-two patients with fertility problems were identified as carriers of small supernumerary marker chromosomes (sSMC). Molecular cytogenetic techniques were used to characterize their chromosomal origin. Together with the other cases available in the literature 111 sSMC cases have now been detected in connection with fertility problems in otherwise clinically healthy persons and characterized for their genetic content. According to this study, in 60% of the cases the sSMC originated from chromosomes 14 or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 15 publications
3
64
2
1
Order By: Relevance
“…The mechanism by which sSMCs influence fertility has not yet been understood (Manvelyan et al, 2008). It has been suggested that sSMCs may lead to reduced fertility in males without additional clinical symptoms in connection with the sSMC (Mulcahy and Jenkyn, 1972;Chandley et al, 1975;Mau et al, 1997;Manvelyan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The mechanism by which sSMCs influence fertility has not yet been understood (Manvelyan et al, 2008). It has been suggested that sSMCs may lead to reduced fertility in males without additional clinical symptoms in connection with the sSMC (Mulcahy and Jenkyn, 1972;Chandley et al, 1975;Mau et al, 1997;Manvelyan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that sSMCs may lead to reduced fertility in males without additional clinical symptoms in connection with the sSMC (Mulcahy and Jenkyn, 1972;Chandley et al, 1975;Mau et al, 1997;Manvelyan et al, 2008). According to population studies, sSMCs are found approximately 2.9 times more often in healthy persons with un-explained infertility compared to the general population (Manvelyan et al, 2008). Manvelyan et al (2008) reported that an enhanced rate of repeated abortions in sSMC carriers or their partners was observed in 22-35% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations